THE CORRELATION BETWEEN STUDENTSâ€™ SELF CONFIDENCE AND THEIR SPEAKING SKILL ( In the Second Grade of the English Education Department of STKIP Garut) - Sapril, Teten Mohamad (Journal Civics & Social Studies, 2017)
The Corellation between Studentsâ€™ Self Confidence and Their Speaking Skill. ( Inthe Second-Grade Students of English Education Department of STKIP Garut)This study was undertaken by the writer because most of English studentsoften got dificulty in English speaking. Especialy in their confident to speakEnglish. To have a good English speaking , the students are expected to be able tobuild,develop and show their confident to use English speaking in any opportunity.Besides that, through self confident the students costumize to use English as daillyCommunication, it is important for the students to get more interaction and practicesin English speak in order they can mastering English speaking skill well.This study was aimed at investigating the corellation between studentsâ€™ selfconfidence and theirsâ€™ speaking skill. It was intended not only to solve the studentsdificulties in speaking English, But also to answer the main question â€œ Is there asignificant corellation between studentsâ€™ self confidence and their speaking skill?â€.The writer used the correlational method to find out and investigate whetherthere was a corellation or not between two variabels and how strong it is. Therespondent , Sixty four students of the second grade of English Education Programof STKIP Garut were selected proporsionl stratified randomly. The study began byassigining the students to answer the self confidence questionaries, then the writercollect the students speaking score from first until third which have provided inEnglish program office. Beside that, the writer clasified category for confidennceand took average speaking score from first until third to support the result of thedata analysis.The instrument include two variabels: Studentsâ€™ self confidence and averageof speaking score list. To analyze the data, the writer used Pearson/Product Testformula to test the corellation and to test hypotesis. The result of the data analysisshowed the coefficient corellation between two variabels is 0,007 (sig = 0,007).Based on this result, it could be concluded that there was a very significantcorellation between studentsâ€™ self confidence and their speaking skill. For thisreason, the researcher purposed some recomendation for the teacher and thestudents of STKIP Garut. The students suggested that they should build,develop,force and show their confidence of practicies in speaking English.